PENERAPAN TEKNOLOGI RIA UNTUK MEMBANGUN APLIKASI WEB DENGAN PENGAKSESAN REALTIME (Studi Kasus : Pemesanan Handphone Online) - Noviyanto, Fiftin; Ashari, Ahmad (Universitas Ahmad Dahlan, 2011)
Today Web technology allow web visitor to interact fully to web based system. The interaction accessibility development aims to make it more attractive and make visitor easier in system usage. One of advantages of web based application is easiness in accessing data that not limited to place and time, while its disadvantage is waiting time for processing user request, so more time process in web application called then required waiting time is more. It is different from desktop based application that require application installation in computer used to access data, however, it has advantage in execution process of real-time instruction, without requiring data access waiting time to server. This research has succeeded in applying RIA technology to build web with instruction response capability same as desktop application in case study of cellular phone reservation. Built system included catalog presentation, filterization, comparation, shopping basket and reservation process. Built application consisted of some layers including data alter as reservation system data storage, presentation later to present product and control layer to manage instruction response.